Vaccination, the only weapon against COVID-19, for the nonce - Mohammad Mujeeb Khan (Journal of Rawalpindi Medical College, 2021)
Epidemics of infectious diseases have always been well documented throughout the human history, particularly by ancient Egypt and Greece and for diseases like smallpox, leprosy, tuberculosis, meningococcal infections and diphtheria. Since the ancient times, the morbidity and mortality of these infectious diseases has profoundly shaped the politics, commerce, culture and social structure of different eras in epidemics. (1) With the beginning of 2020, world has encountered a new challenge, with the name of Covid-19. Commencing from Wuhan city of China, this disease spread like wildfire within a matter of next few months, with a rising death toll and serious consequences on the entire globe. The impact of COVID-19 on the population was no less than terror and shock. Since COVID-19 disease kept on spreading via aerosol and droplet infections, World Health Organization (WHO) declared emergency and along with other health agencies emphasized on respiratory hygiene i.e. covering the nose and mouth with a mask and using cough etiquettes in addition to standard precautionary measures. Social distancing was emphasized. Different rapid treatment guidelines were developed and practiced across the globe, with no definitive management guaranteeing the recovery cent per cent. Where a number of interventions were being tried and tested, attention was diverted towards vaccination since it had always been contemplated to be the integral in control of many infectious diseases.(2) Vaccination is envisaged as one of the most effective public health interventions for preventing and saving lives of from different infectious diseases and promoting good health. Hence scientists from all over the world got involved in rapid and expeditious development of vaccines against this novel disease.